Otton III - Strzelczyk, Jerzy (Wroclaw : Zaklad Narodowy im. Ossolinskich, Wydawn., 2000)
A biography of Otto III, The German Holy Roman Emperor who died in 1002.
Keywords: Otto -- III, -- Holy Roman Emperor, -- 980-1002.; Germany -- History -- Saxon House, 919-1024.